The endogeneity of optimum currency areas in light of pan-European intra-industry trade patterns and business cycle synchronicity - Frank Niklas Steinert; Wilhelm Althammer (Empirica, 2024)
The creation of a common European currency has been scrutinized in the context of optimum currency area theory since its origin in Mundell ( 1961 ). The debate gained particular prominence in light of the endogeneity hypothesis (Frankel and Rose 1998 ), which argues that once two countries establish a common currency, their economic structures and cycles increasingly align due to strengthening intra-industry trade. By contrast, the specialization hypothesis (Eichengreen 1992 ; Krugman and Venables 1996 ) argues that the creation of a currency union will predominantly increase inter-industry trade, ultimately lowering business cycle correlation. To test these views, we establish several indices of bilateral trade intensity across EU members using input–output data, measuring gross and so-called value-added trade, which also considers the contribution of intermediary goods in the production of final exports. The results of the fixed effect panel data framework indicate a strong and robust empirical relationship between growth correlations and intra-industry trade, much in line with both Mundell's and Frankel and Rose's theories. However, we cannot establish a similarly robust relationship between total trade intensity and growth correlations. We reconcile these results by identifying a statistically significant relationship between economic alignment and trade when only considering industrial production, highlighting the importance of pan-European industrial supply chains for European economic integration. Rerunning our regression framework on the subsample of the eurozone indicates that the common currency area displayed even stronger properties of an optimum currency area than the entire European Union.
Keywords: 330